2019
DOI: 10.1177/1352458518819098
|View full text |Cite
|
Sign up to set email alerts
|

Severe meningo-/encephalitis after daclizumab therapy for multiple sclerosis

Abstract: Background: Daclizumab is a monoclonal antibody that binds the high-affinity interleukin-2 receptor and was approved for the treatment of relapsing multiple sclerosis. Due to severe inflammatory brain disorders, the approval was suspended in March 2018. Objective and Methods: This retrospective cohort study summarizes clinical, laboratory, radiological, and histological findings of seven patients who developed meningo-/encephalitis after daclizumab therapy. Results: Patients presented with encephalitis and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Especially for IL-2, immunomodulatory drugs are expected to induce stronger responses by targeting their action on components of the immune system. A marked decrease of seroreactivity towards LAM in patients who did not follow any therapy may occur as a spontaneous regression similar to natural healing observed in pulmonary tuberculosis [12] and linked to the return of MAP to latent infection phases in concert with MS relapse recovery. Even though the course of MAP infection in humans is unclear, typical symptoms of paratuberculosis affecting ruminant animals consist of transient active disease associated with a massive production of cytokines including IL-2 and intervals when the mycobacterium assumes intracellular phenotype [29].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Especially for IL-2, immunomodulatory drugs are expected to induce stronger responses by targeting their action on components of the immune system. A marked decrease of seroreactivity towards LAM in patients who did not follow any therapy may occur as a spontaneous regression similar to natural healing observed in pulmonary tuberculosis [12] and linked to the return of MAP to latent infection phases in concert with MS relapse recovery. Even though the course of MAP infection in humans is unclear, typical symptoms of paratuberculosis affecting ruminant animals consist of transient active disease associated with a massive production of cytokines including IL-2 and intervals when the mycobacterium assumes intracellular phenotype [29].…”
Section: Discussionmentioning
confidence: 72%
“…Low doses of IL-2 have been successfully employed as add-on MS therapy [10], while the detection of increased IL-2 levels in MS patients has led to the development of therapeutic approaches targeting IL-2 receptor [11]. However, further observations have demonstrated that side effects such as severe inflammatory brain disorders [12,13] and resistance to antagonistic antibody therapies that target receptors at the cell surface may arise in a relatively short time [14]. Moreover, high expression of IL-2 has been reported in animals after Mycobacterium tuberculosis and MAP infection [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In SELECTED, most AEs observed with daclizumab beta were mild or moderate in severity and did not increase with long-term exposure. There were no observed cases of inflammatory encephalitis, meningoencephalitis, fulminant liver failure, or fatal liver injury [8,27]. The efficacy of daclizumab beta on clinical and radiologic MS disease activity outcomes was sustained across yearly treatment intervals for up to 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…IL2RA is the target of the therapeutic antibody Daclizumab, which is known to be clinically effective in the treatment of MS (Wynn et al . 2010;Bielekova et al 2004) , but has been withdrawn due to severe side effects including encephalitis (Stork et al 2019;Bielekova et al 2006) ; (Giovannoni et al 2016;Curto et al 2016;Abbas et al 2011) . A second antibody used to treat MS (Natalizumab), which targets the α4β1 integrin, has been associated with a small number of cases of progressive multifocal leukoencephalopathy (PML), but is still licensed (Bloomgren et al .…”
Section: Elucidating Disease Etiology and Inferring Drug Targetsmentioning
confidence: 99%